The origin of neotectonics on the lunar nearside - Valantinas, A.; Schultz, P.H. (Geology, 2020)
New observations of wrinkle ridges on the nearside maria of the Moon display signs of ongoing ridge modification. In association with the wrinkle ridges, we observed an absence of superposed craters, narrow (<30 m) lobate scarps and graben, and thermal anomalies related to exposures of meter-size blocks. Many of these active wrinkle ridge systems are well beyond the influence of mascon basins and unrelated to any global tectonic pattern. Nevertheless, they spatially correlate with ancient deep-seated dike intrusions on the lunar nearside revealed by gravity data analysis. We propose that this active nearside tectonic system (ANTS) reflects ongoing reactivation of an ancient system related to offset antipodal effects from the South Pole–Aitken basin.